Recent Developments in Applied Electrostatics : Proceedings of the Fifth International Conference on Applied Electrostatics, November 2-5, 2004, Shanghai, China - Keping, Sun; Gefei, Yu (Elsevier, 2004)
Applied Electrostatics (ICAES 2004).